Reliability and validity of 3D body scanning for anthropometric profiling - Forchino, F.; Galloway, S. D. R.; Douglas, A.; Hazeldine, A.; Brandner, C.; Bourdon, P. C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Surface anthropometry is widely used to assess and monitor athletes due to its strong relationship with sporting success. Furthermore, some measures are frequently used for talent identification in certain sports. Recently, 3D body scanning has emerged as a promising alternative to traditional surface measurements, offering greater accuracy and precision. However, various steps in the 3D data collection process and analysis can potentially introduce error. Therefore, assessing the reliability and validity of the 3D body scanning (3D) technology is required to ensure best practice for its use in the assessment of anthropometric variables. Methods: Physical measurements (PM) were collected using both traditional ISAK protocols and 3D body scans on 30 highly trained young male athletes (age 15.8 ± 1.7 y, body mass 62.9 ± 15.1 kg, height 174.0 ± 7.9 cm). Digital data analyses of the 3D scans were carried out in duplicate by 3 trained technicians. Interclass correlation coefficients (ICC) and relative technical error of measurements (%TEM) were calculated to assess the reliability of the 3D analyses between technicians, and also between the 3D and PM data. Pearson correlation and a paired sample t test (p 0.05) were also conducted. Results: There was no significant difference for intra-retest reliability (ICC: 037 - 1.00) and inter-rater reliability for the 3D analyses (ICC: 0.63 - 1.00) or between each technicians 3D data analyses and the PM (ICC: 0.47 - 1.00). 3D intra-tester %TEMs ( 1%) showed agreement for height and 4 body lengths. Inter-tester %TEMs ( 1.5%) showed agreement for height and 5 body lengths between 3D data analyses and PM. The correlation analyses revealed moderate to strong but statistically significant Pearson correlation coefficients (range: 0.67 - 0.99) for all variables. Results of the paired t tests were significant for several variables, indicating a significant difference between the 3D and PM. Discussion: This study shows that there is evidence for the repeatability of 3D measurements when assessing height, breadths, and several limb lengths and girths. Even though, 3D scans can easily be reviewed post-collection as many times as needed, it cannot exactly replicate the techniques used for PM (i.e. ISAK protocols). Therefore, a combination of both digital and physical methods should be considered.